Organization of various types of treatment and preventive assistance to the population. Outpatient, inpatient and ambulance : methodical recommendations to prepare 3–4 year students for independent work for the discipline of «Social Medicine, organization of health care» [Electronic resourсe] - Bobrova, Oksana Vyacheslavivna; Tsukor, Nataliia Hryhorivna; Боброва, Оксана Вячеславівна; Цукор, Наталія Григорівна (Kharkiv : V.N. Karazin Kharkiv National University, 2024)
The presented methodical recommendations for those seeking higher education highlight the topics devoted to an important section of social medicine and the organization of health care - the principles of organizing various types of medical and preventive care for the population, namely outpatient, inpatient and emergency. The methodical recommendations were developed on the basis of the current regulatory documents regarding the reform of health care of Ukraine. The stages of providing medical care to the population, the essence of the stages, as well as the main regulatory and legal documents regulating the activity of health care facilities in the conditions of health care reform, their list and content are described. The methodological recommendations are made in accordance with the educational and professional training program for higher education applicants of the medical faculty of the 3rd year of the university, qualification level Master, in the field of knowledge 22 «Health care», specialty 222 «Medicine». The material in the methodological recommendations is presented in English, the structure of the recommendations corresponds to the methodology of conducting classes.

У представлених методичних рекомендаціях для здобувачів вищої освіти висвітлені теми, присвячені важливому розділу соціальної медицини та організації охорони здоров`я - принципам організації різних видів лікувально-профілактичної допомоги населенню, а саме - амбулаторної, стаціонарної та екстреної. Методичні рекомендації розроблені на основі діючих нормативних документів щодо реформування охорони здоров'я України. Описані етапи надання медичної допомоги населенню, сутність етапності, а також основні нормативно-правові документи, що регламентують діяльність ЛПЗ в умовах реформування охорони здоров'я, їх перелік і зміст. Методичні рекомендації складені відповідно до освітньо-професійної програми підготовки здобувачів вищої освіти медичного факультету 3 курсу університету, кваліфікаційного рівня Магістр, в галузі знань 22 «Охорона здоров’я», спеціальність 222 «Медицина». Матеріал у методичних рекомендаціях викладений англійською мовою, структура рекомендацій відповідає методології проведення занять.
Організація різних видів лікувально-профілактичної допомоги населенню. Амбулаторно-поліклінічна допомога, стаціонарна та швидка допомога : методичні рекомендації до самостійної роботи для здобувачів вищої медичної освіти 3–4 року навчання з дисципліни «Соціальна медицина, організація охорони здоров’я» [Електронний ресурс]
Електронне навчальне видання комбінованого використання. Можна використовувати в локальному та мережному режимі
Keywords: MEDICINE; types of medical and preventive care for the population; outpatient medical care; inpatient medical care; emergency medical care; family medicine; види лікувально-профілактичної допомоги населенню; амбулаторна медична допомога; стаціонарна медична допомога; екстрена медична допомога; сімейна медицина